A Exploratory Data Analysis (EDA) of Social Aid Recipients in Murung Raya District Central Kalimantan Province with Machine Learning Approach: Analisis Data Eksplorasi (EDA) Penerima Bantuan Sosial di Kabupaten Murung Raya Provinsi Kalimantan Tengah dengan Pendekatan Machine Learning - Regina; M. Riko Anshori Prasetya; Ahmad Hidayat (INSTALL: Information System and Technology Journal, 2024)
Various kinds of problems often occur in programs implemented by the government, one of which is the problem that often arises is the uneven distribution of social assistance carried out to people with low economic levels, poverty is the main problem being faced by all countries in the world, including Indonesia. The purpose of implementing the dataset of social assistance recipients using EDA. To find the correlation of 4 variables, namely Number of Population, Number of Recipients, Occupation, and Age in the dataset of social assistance recipients in Murung Raya District, Central Kalimantan Province, with a machine learning approach. Then the research method used here is quantitative methods and experiments with machine learning approaches. So by using the EDA method on data on social assistance recipients in Murung Raya Regency, Central Kalimantan Province, it can be seen that the variable Number of population has.